Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)\(3x\left(x-2\right)+2\left(2-x\right)=0\)
\(\Leftrightarrow3x\left(x-2\right)-2\left(x-2\right)=0\)
\(\Leftrightarrow\left(3x-2\right)\left(x-2\right)=0\)
\(\Rightarrow\orbr{\begin{cases}3x-2=0\\x-2=0\end{cases}}\)\(\Rightarrow\orbr{\begin{cases}x=\frac{2}{3}\\x=2\end{cases}}\)
b)\(5x\left(3x-1\right)+x\left(3x-1\right)-2\left(3x-1\right)=0\)
\(\Leftrightarrow\left(3x-1\right)\left(5x+x-2\right)=0\)
\(\Leftrightarrow\left(3x-1\right)\left(6x-2\right)=0\)
\(\Leftrightarrow2\left(3x-1\right)\left(3x-1\right)=0\)
\(\Leftrightarrow\left(3x-1\right)^2=0\Rightarrow3x-1=0\Rightarrow x=\frac{1}{3}\)
a/3x(x-2)+2(2-x)=0
=>(2-3x)(2-x)=0
=>\(\orbr{\begin{cases}2-3x=0\\2-x=0\end{cases}}\)=>\(\orbr{\begin{cases}3x=2\\x=2\end{cases}}\)=>\(\orbr{\begin{cases}x=\frac{2}{3}\\x=2\end{cases}}\)
b/5x(3x-1)+x(3x-1)-2(3x-1)=0
=>(5x+x-2)(3x-1)=0
=>(6x-2)(3x-1)=0
=>\(\orbr{\begin{cases}6x-2=0\\3x-1=0\end{cases}}\)=>\(\orbr{\begin{cases}6x=2\\3x=1\end{cases}}\)=>x=\(\frac{1}{3}\)
a)
\(\Rightarrow x\left(x-5\right)=0\)
\(\Rightarrow\left[\begin{array}{nghiempt}x=0\\x-5=0\end{array}\right.\)
\(\Rightarrow\left[\begin{array}{nghiempt}x=0\\x=5\end{array}\right.\)
b)
\(\Rightarrow3x\left(x-2\right)-2\left(x-2\right)=0\)
\(\Rightarrow\left(x-2\right)\left(3x-2\right)=0\)
\(\Rightarrow\left[\begin{array}{nghiempt}x-2=0\\3x-2=0\end{array}\right.\)\(\Rightarrow\left[\begin{array}{nghiempt}x=2\\x=\frac{2}{3}\end{array}\right.\)
c)
\(\Rightarrow\left(3x-1\right)\left(5x+x-2\right)=0\)
\(\Rightarrow\left(3x-2\right)^2.2=0\)
\(\Rightarrow3x-2=0\)
\(\Rightarrow x=\frac{2}{3}\)
b, \(\left(x-5\right)\left(x-4\right)-\left(x+1\right)\left(x-2\right)=7\)
\(\Rightarrow x^2-9x+20-x^2+x+2=7\)
\(\Rightarrow-8x+22=7\)
\(\Rightarrow-8x=-15\)
\(\Rightarrow x=\frac{15}{8}\)
c, \(\left(3x-4\right)\left(x-2\right)=3x\left(x-9\right)-3\)
\(\Rightarrow3x^2-10x+8=3x^2-27x-3\)
\(\Rightarrow3x^2-10x-3x^2+27x=\left(-3\right)+\left(-8\right)\)
\(\Rightarrow17x=-11\)
\(\Rightarrow x=-\frac{11}{17}\)
d, \(\left(x-3\right)\left(x^2+3x+9\right)+x\left(5-x^2\right)=6x\)
\(\Rightarrow x^3+3x^2+9x-3x^2-9x-27+5x-x^3=6x\)
\(\Rightarrow6x=-27\)
\(\Rightarrow x=-\frac{27}{6}\)
\(\Rightarrow x=-\frac{9}{2}\)
e, \(\left(3x-5\right)\left(x+1\right)-\left(3x-1\right)\left(x+1\right)=x-4\)
\(\Rightarrow3x^2-2x-5-3x^2-2x+1=x-4\)
\(\Rightarrow-4=x-4\)
\(\Rightarrow x=0\)
b) (x - 5)(x - 4) - (x + 1)(x - 2) = 7
<=> x2 - 9x + 20 - x2 + x + 2 - 7 = 0
<=> 8x - 15 = 0 <=> x = 15/8
c) (3x - 4)(x - 2) = 3x(x - 9) - 3
<=> 3x2 - 10x + 8 = 3x2 - 27x - 3
<=> 17x = -11 <=> x = -11/17
d) (x - 3)(x2 + 3x + 9) + x(5 - x2) = 6x
<=> x3 - 27 - x3 + 5x - 6x = 0
<=> x = -27
e) (3x - 5)(x + 1) - (3x - 1)(x + 1) = x - 4
<=> (x + 1)(3x - 5 - 3x + 1) - x + 4 = 0
<=> -4x - 4 - x + 4 = 0 <=> x = 0
b)3x2 - 3x(x - 2)=36 c) (3x2 - x + 1)(x - 1)+ x2(4 - 3x) = 5/2
3x2 - 3x2 + 6x= 36 3x3 - 3x2 - x2 + x + x - 1 + 4x2 - 3x3= 5/2
6x=36 =>x=36 : 6= 6 (3x3 - 3x3) + (-3x2 - x2 + 4x2) + (x + x) - 1= 5/2
2x - 1= 5/2 =>2x= 5/2 + 1= 7/2
x= 7/2 : 2 =7/4
ta có: (3x-1)^2=(x-1)^2
=>9x²-6x+1=x²-2x+1
=>9x²-6x+1-x²+2x-1=0
=>8x²-4x=0
=>4x(2x-1)=0
=>4x=0 ; 2x-1=0
=>x=0 ; x=1/2
vậy x = (0,1/2)